Impian Carpet / Norhaliza Ahmad ... [et al.] - Ahmad, Norhaliza; Anuar, Nurul Azwana; Ismail, Shahanun; Jamil, Siti Haryati; Othman, Rosnida (2002)
Carpet is originally comes from Iran. Arabians come too Malay State to trade carpet business. Since from that, people in Malay State interested in using carpet. They feel that if they have carpet the standard of living is higher. Then, it grows up until now. The most imported carpet is from Belgium because that country produces more carpets than other country. Impian Carpet is a business that will begin operations in 2005. Impian Carpet is serves in Penang especially houses, restaurants, hotels, mosque and school. The recovery of our economy now gives many advantages to investors and entrepreneurs to enter in new business. Nowadays, many new development areas in Penang have been rising. So, Impian Carpet has a bright future in selling of intermediate, classic and exclusive, and contract carpet.